Relationships between the risk of emerging zoonotic diseases and the architecture of interactions between people, domestic animals and wildlife in the Pantanal - GIULIA ARMANI ARAUJO (2024)
There is a growing acknowledgment of the public health risks linked to human interactions with both wild and domestic animals. Approximately 70% of Emerging Zoonotic Diseases (EZDs) and many recent pandemics can be traced to human-animal interactions. Factors such as social dynamics and gender roles significantly influence these interactions, affecting the epidemiology of infectious diseases. The perception of EZD risks varies across social groups, with socially vulnerable populations experiencing heightened risks due to barriers – such as accessibility to health services and education. The role of landscapes in zoonotic disease dynamics is also emphasized. Anthropogenic land use changes disrupted biodiversity and altered human-animal interaction patterns. Prior studies suggested that this context could lead to increased pathogen transmission and heightened interaction frequencies. However, responses in interaction networks are viewed as context-dependent, influenced by socio-economic factors and cultural practices. These factors are believed to shape agricultural structures and subsequently affect species abundance and public health risks. This dissertation comprises two interconnected chapters that investigate socio-economic, gender, and environmental factors in the interactions between people and animals in the Pantanal. An appendix presents a risk assessment framework for emerging zoonotic diseases in the Pantanal wetland, developed collaboratively with researchers. The first chapter examines risk perception and gender dynamics in the Pantanal. It posits that while men have more interactions with animals, they possess lower risk perception; in contrast, women have heightened risk perception tied to caretaking roles. The study anticipated a negative correlation between risk perception and interaction frequency, expecting Riverine Communities to show more interactions due to higher biodiversity. The results revealed that men interacted more with animals than women resulting in a richer network then, and Riverine Communities exhibited greater richer than those in Settlements. Nevertheless, perceived risk levels did not vary significantly between genders or social groups. Fieldwork indicated distinct gender roles, highlighting greater gender equality in Riverine Communities compared to Settlements. The second chapter investigates how gradients of native vegetation impact human-animal interaction networks in agrarian Settlements. The hypothesis suggested a positive correlation between interactions and the amount of native vegetation (NV). Network analysis revealed that only a small portion of interactions could be explained by the NV gradient, and the network displayed degree assortativity, indicating that nodes with similar interaction levels tend to connect. There was no significant relationship between shared interactions, NV, and property distances. While the evidence did not strongly support the hypothesis, factors like functional connectivity through patches of NV were suggested. The study emphasises the need to understand human-animal interactions in the Pantanal to inform effective public health and conservation policies. It advocates for a participatory conservation model involving local communities in policymaking, promoting the co-production of health and conservation strategies to enhance acceptance and effectiveness. The significance of network metrics in epidemiology and conservation is noted, along with a call for collaboration with global zoonosis databases for better disease outbreak tracking. It recommends integrating biodiversity conservation into One Health programmes, focusing on gender, changing human behaviours, and raising awareness of biodiversity benefits to mitigate zoonotic disease risks while supporting conservation efforts. Key Words: One Health; Conservation; Socio-metacommunity; Zoonosis